Palaeoenvironmental evolution, sea-level changes and Human occupation in Lemnos Island during last 6000 years (North Aegean Sea, Greece) - Fouache, Eric (2012)
The mapping demonstrates the abundance of glacial landforms in the study area. In addition to familiar forms such as moraines and U-shaped valleys, forms previously unknown in the Andes – trimline moraines – could be detected. Their age determination is in progress at the moment. On the basis of the mapped glacial forms, it was possible to reconstruct equilibrium lines for a sampling of several localities, which, along with the chronological classification, can shed light on the climatic change during past phases of glaciation. In the western Pampas of Argentina (33 – 36 S, San Luis province, South America) there are extensive late Quaternary aeolian sand deposits forming diverse depositional systems. This region is almost completely covered by a savanna dominated by Prosopis caldenia and profuse grass-land (Espinalphytogeographical province). The northern region, from the distal piedmont of the San Luis ranges to about the alluvial plain of the Quinto River, is mostly covered by aeolian sand sheets, associated with ephemeral arroyos and, occasionally, with partially eroded dunes. From here to the south, and passing transitionally to the southern and central Pampas of Córdoba and La Pampa provinces, the landscape is dominated by diverse suite of dunes. The most conspicuous feature of the central area is the presence of large (up to 4 km long), compound parabolic dunes and blowouts, with two main orientations. One set of parabolic dunes accret-ted with southeasterly paleowinds, whereas most of the parabolic dunes and blowouts in the eastern region were formed by northeasterly paleo-winds. Both directions are consistent with present wind data (1995-2004). Several parabolic and blowout depressions create freshwater lakes, likely filled by groudwater. Southern San Luis province presents complex linear dunes, with a NNW trending that extends for more than 25 km. This linear pattern is formed by the coalescence of parabolic dunes, which indicate southeasterly paleowinds. Sedimentological analysis and OSL dating reveal episodic sand sheet deposition between ca. 33 and 25 ka, with a potentially high lake stand at ca. 11.4 ka. Dune reactivation, possible developing parabolic dunes, appears to have occurred during different times of the Holocene (ca. 9.7 to 1.6 ka). This study reveals this aeolian landscape reflects significant paleoenviromental changes along the late Pleistocene-Holocene, adding new chronological constrained deposits to compare and study past arid systems.